The Influence of Sex, Age, and Repeated Measurement on Pixel-Based Measures of Pharyngeal Area at Rest - Smaoui, Sana; Mancopes, Renata; Simmons, Michelle M; Peladeau-Pigeon, Melanie; Steele, Catriona M (Journal of speech, language, and hearing research, 2023)
Videofluoroscopic (VFSS) measurements of pharyngeal swallow mechanics can differentiate age- and disease-related changes in swallowing. Pharyngeal area at rest (PhAR) may differ in people with dysphagia, although its impact is not clear. Before the role of PhAR in dysphagia can be explored, it is important to establish whether PhAR remains stable across repeated measures in healthy adults, and varies as a function of sex or age. We hypothesized that healthy adults would show stable PhAR across repeated measures, but that larger PhAR would be seen in men versus women and in older versus younger adults. We collected VFSS data from 87 healthy adults (44 men, = 46 years, range: 21-82). Trained raters identified the swallow rest frame after the initial swallow of each bolus and measured unobliterated pharyngeal area on these frames, in %(C2-4) units. Repeated-measures analyses of variance with a factor of sex, a covariate of age, and a repeated factor of task repetition were performed across the first 12 available measures per participant ( = 1,044 swallows). There were no significant variations in PhAR across repeated measures. A significant Sex × Age interaction was seen ( = .04): Males had significantly larger PhAR than females ( = .001), but females showed larger PhAR with advancing age ( = .47). These data confirm stability in PhAR across repeated measurements in healthy individuals. However, significant sex and age differences should be taken into consideration in future studies exploring the role of PhAR in people with dysphagia. https://doi.org/10.23641/asha.22043543.